Evaluation of microalgae from himalayan region for nutraceutical activities - AKANSHA BAJPAI; VIJAY KUMAR GARLAPATI; RAKESH SINGH GOUR; ANIL KANT (International Journal of Pharma and Bio Sciences, 2017)
Microalgae serve as a predominant biological source for nutraceutical compounds along with the lipids and dyes.In the presentstudy, microalgal species from the Himalayan region, India have been evaluated for nutraceutical activities such as carbohydrate, protein, phenolic, flavonoid contents and DPPH activities. The evaluation showcased that Scendesmus dimorphus was found to be the highest producer of protein andcarbohydrate than the Scendusmus quadricauda and Chlorella sp. Among the microalgal species, Chlorella sp. was found to have a more antioxidant, phenolics, flavonoid,and DPPH activities over Scendusmus sp. y. Overall, the present study showcase the unexplored potential of microalgae for various nutraceutical activities. This unexplored algal source may serve as an untappedresource for nutritional and food-biotech communities to do research for its incorporation as a palatable feed material and also as an aquatic, and animal feed.